The Effects of Various Planting Media and Organic Fertilizers on the Growth and Yield of Purslane (Portulaca Oleracea L.) - F. Deru Dewanti; Sukendah Sukendah; Puji Lestari Tarigan; Ahmad Yunus (Jurnal Penelitian Pendidikan IPA, 2023)
Purslane has many benefits as food or raw material for medicine. It is rich in beneficial compounds, such as omega-3 and vitamins. However, it has not been cultivated yet. Organic input in cultivation is essential to ensure food safety for humans. Using organic inputs can avoid the yield from chemical and biological contaminants that can threaten health. Thus, the source of growing media and fertilizer must be considered. Because the use of synthetic chemicals has residues that are harmful to the environment and human health. This research sought to identify the best combination of growing media and organic fertilizer to increase purslane yield. The experiment was conducted with a randomized block design with 2 factors and 3 replications. Organic fertilizers (guano, cow urine, and rabbit urine) and planting media (soil, soil + husk charcoal, soil + compost, and soil + husk charcoal) were the treatments assessed. The observation variables were planting media analysis, the number of leaves and branches, growth diameter, and fresh weight. The results show that the planting medium and organic fertilizer did not significantly affect the measured growth parameters. The single variable of organic fertilizer made a difference in growth diameter and fresh weight. Rabbit urine produced in the highest growth diameter, and guano produced in the highest fresh weight The single variable of organic fertilizer made a difference in growth diameter and fresh weight. Rabbit urine produced in the highest growth diameter, and guano produced in the highest fresh weight The single variable of organic fertilizer made a difference in growth diameter and fresh weight. Rabbit urine produced in the highest growth diameter, and guano produced in the highest fresh weight